Comparative study between positive position feedback and negative derivative feedback for vibration control of a flexible arm featuring piezoelectric actuator. (5th July 2017) - Syed, Hassaan Hussain
Positive position feedback control is the most common resonant control technique that has been studied for last three decades. As a low-pass filter, positive position feedback is very sensitive to low-frequency disturbances. To overcome this shortcoming of positive position feedback controller, negative derivative feedback controller, which acts as a bandpass filter and can effectively control the lower and higher frequency disturbances, has been developed recently. So far, there is no comparison work between positive position feedback and negative derivative feedback on flexible manipulator system. Consequently, to fill this gap, in this article, both positive position feedback and negative derivative feedback controllers are applied experimentally and analysed in terms of settling time and vibration attenuation at different damping ratios on a single link flexible manipulator featuring piezoelectric actuator. Moreover, robustness with respect to natural frequency variation is studied for the first time on flexible manipulator system. Based on experimental study conducted on the particular system developed in this article, it has been observed that negative derivative feedback controller is more effective than positive position feedback controller based on evaluated performance measures.